Analisis Hukum Pelaksanaan Peraturan Menteri Agraria Dan Tata Ruang/Kepala Badan Pertanahan Nasional Nomor 6 Tahun 2018 Di Kantor Pertanahan Kota Medan - Suci Rahmadani; Isnaini Isnaini; M. Ridha Haikal (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This article aims to analyze and examine the legal arrangements of mechanisms and constraints as well as obstacles to the implementation of Complete Systematic Land Registration (PTSL) at the Medan City Land Office. This study uses empirical legal research that is descriptive analysis. The approach used in this study is a statutory approach and a conceptual approach. This study collected primary data obtained by using field research and secondary data obtained by using library research, which were then analyzed qualitatively. The results of this study indicate that the implementation of PTSL is regulated in the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 6 of 2018 concerning Complete Systematic Land Registration. The implementation of PTSL in Medan City is based on the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 6 of 2018 and also its implementation is in accordance with the Complete Systematic Land Registration Technical Guidelines Number 1/Juknis/-100.HK.02.01/I/2022 January 26, 2022. Obstacles and obstacles include, Lack of Public Awareness of the Importance of Land Certificates, Incomplete requirements and land certificates in accordance with the history of their acquisition from PTSL Participants, Public Objections Regarding BPHTB Payments, Absentee Land and Abandoned Land. These constraints/obstacles make the implementation of PTSL activities too late to be completed in accordance with a predetermined target time.